The Effect of Material Type and Location of an Orthodontic Retainer in Resisting Axial or Buccal Forces - Ohtonen Jaana; Lassila Lippo; Säilynoja Eija; Vallittu Pekka K. (MDPI, 2022)
The purpose of this study was to investigate the effect of retainer material and retainer position on a tooth to resist movement of the tooth in a simulation model. Bidirectional continuous glass fiber-reinforced composite (FRC) retainers and control retainers of steel wires were tested. The FRC retainers had a polymer matrix of bisphenol-A-glycidyldimethacrylate (bis-GMA) and poly(methylmethacrylate) (PMMA), and it was cured with a photoinitiator system. The retainers were adhered to a lower jaw Frasaco model in two different positions. Resistance against the movement of one tooth was measured from two directions. The average load values within the FRC retainer groups were higher than within the metal retainer groups. The load values for the groups loaded from the axial direction were higher than those loaded from the buccal direction. FRC retainers, which were located 1–2 mm from the incisal edge, showed higher load values than those located 4–5 mm from the incisal edge. There was a significant difference in load values between FRC retainers and metal retainers (p < 0.01). The wire position and the direction of force also had significant effects (p < 0.01). There were no significant differences between metal retainer groups. The results of this study suggest that metal retainers are more flexible, allowing for tooth movements of larger magnitude than with FRC retainers. View Full-Text
Keywords: orthodontic FRC retainer; HS glass; composite; stainless steel; mechanical test